Development of Portable Micro Medical Negative Pressure Therapy Instrument - Donghong Zheng, Yanyi Zhu, Cu Zhao, Chaomin Chen (Forest Chemicals Review, 1970)
Vacuum sealing drainage (VSD) and vacuum-assisted closure (VAC) are two critical technologies that have been widely used in recent years to treat severe soft tissue injury, osteomyelitis, acute severe pancreatitis, severe abdominal trauma, intra-abdominal infection, body surface abscess, old hematomas, skin ulcers, pressure sores, among other conditions. At the moment, clinical applications of negative pressure therapy instruments have a large volume, an unstable negative pressure, high power consumption, noise, cumbersome operation, and a single mode of operation. The portable micro medical negative pressure therapy instrument studied in this article has been improved based on the conventional negative pressure therapy instrument, and has a simple operation, stable negative pressure, a variety of working modes, adjustable pressure, good safety performance, high intelligence, light weight, small volume and portability.